Systemic yield risk and spatial index correlations: relevant market area for index-based contracts - Myyrä, Sami; Pietola, Kyösti; Jauhiainen, Lauri (Taylor & Francis, 2011)
This article estimates spatial correlation of growing degree days (GDDs), accumulation of rainfall and regional yields as well as the observed crop damage payments in Finland. The results suggest that the spatial correlations are the highest and the most persistent for the GDDs. The correlations are the lowest and they decrease quickly with distance for rainfall-based measures, as expected. Also, regional yields and the distribution of crop damage compensations have large regional heterogeneity and low spatial correlations that decrease quickly with the distance. Our results suggest, therefore, that the market potential, in terms of the relevant market area around each measurement point, would be the highest for temperature-based contracts and the lowest for rainfall-based contracts. The relevant market area around a single measurement point is estimated ninefold for accumulation of degree growing days as compared to accumulation of rainfall. Rainfall-based insurance contracts should therefore be tailored to a large number of measurement points, so that a potential buyer/seller could choose the most relevant measurement point in his close vicinity. Large spatial heterogeneity and low spatial correlation in yields further indicate that systemic behaviour might not be as dominant factor as expected in the breakdown of the private crop insurance market in the Finnish production environment.
Keywords: Ma; tehoisa lämpösumma; sato; lämpösumma; sade; markkinatutkimus; yields; markets; precipitation; weather derivatives; growing degree days; spatial correlation; yield; relevant markets